An empirical investigation on the determinants of macroeconomics that influence the stock trade turnover ratio in Malaysia / Muhammad Izzuddin Ruslan - Ruslan, Muhammad Izzuddin (Faculty of Business and Management, Universiti Teknologi MARA, 2015)
This paper studies the relationship between macroeconomic factors and the stock trade turnover ratio in Malaysia using survey from World Bank Data for 1993 until 2012. We argued in determine a favorable functional form of turnover ratio for stock trade for each year, thus, applying the time series of the model parameter in term of macroeconomics factors as this better allow us to take into account unaffected variables in the time series. Estimates from model that relate the stock trade turnover ratio to the selected variables in first differences is Inflation, Consumer Price Index and Exchange rate have significant effect on the stock trade turnover ratio. Compared to the commonly used method of modeling the turnover ratio of stock trade directly, our approach indicates that there was no clear cut relationship between macroeconomic factors and stocks trade turnover ratio in Malaysia for the last 20 years.